Pelatihan Pembuatan VCO Sebagai Upaya Peningkatan Nilai Tambah Kelapa di Desa Simaeasi - Listari Harefa; Natalia Kristiani Lase; Niatman Harefa; Lukas Lisman Gulo; Darman Laia; Tiesland Zebau; Marni Putri Gea; Septin Melindra Gulo; Wince Amsyah Natalia Zai; Ester Twenty Aprilian Zendrato (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
is still limited to household consumption and fresh sales, resulting in low economic value. To increase the added value of coconuts and empower the community, training on Virgin Coconut Oil (VCO) production was conducted for 30 PKK members and 9 village officials. This activity was held on June 24, 2025, at the Simaeasi Village office, using lecture methods, direct practice, and technical assistance. The training covered all stages of VCO production, from coconut selection, grating, coconut milk pressing, fermentation, sedimentation, and the oil refining process. The training results showed that participants experienced a significant increase in knowledge and skills. From 5 mature coconuts, approximately 300 mL of VCO was produced with clear characteristics, coconut aroma, and not rancid. Economic simulations showed that the selling value of VCO is much higher than that of fresh coconuts. Thus, this training successfully increased the community's capacity in coconut processing and opened up new business opportunities based on home industries.